Seminal Oxidative Stress Markers and Fertilization Rate in Sub fertile Male Undergo Assisted Reproductive Technique - Ban J. Edan (Journal of Global Pharma Technology, 2017)
Objectives: The aim of this research is to examine effect oxidative stress in seminal plasma on fertilization rate in assisted reproductive technique (ART) Methods 70 men attended to fertility center in Al-sadder teaching hospital were rolled in this study .semen analysis was done according to the WHO 2010 guidelines. After analysis the results of SFA were classified as the nospermia, Oligospermia, Oligoasthenospermia and normospermia. Seminal free radicals and antioxidants were measured by spectrophotometric absorbance assay. Results MDA was insignificantly and negatively associated with sperm concentration and highly active motile sperm while CAT and GSH was insignificantly and positively associated with sperm concentration and highly active motile sperm (p>0.05). Oxidative stress parameters in different SFA abnormality shows MDA level insignificantly elevated in sub fertile men with abnormal SFA than normal one. Whereas CAT and GSH were in significantly lesser in sub fertile men with abnormal SFA than normal one. Patients with normal SFA had about five time more fertilization rate than patients with abnormal SFA (odds ratio= 5.585 (CI .529 -59.003)). Universal regression analysis was done to show the effect of measured factors on fertilization rate, count and percentage of active sperm was the most effective factor on FR. Conclusion Inadequate antioxidant protection and elevated oxidative stress destruction effect on semen quality and ultimately o fertilization rate and ART outcome.Keywords: Malondialdehyde (MDA), Antioxidant Enzymes, Reduced Glutathione (GSH), Catalase (CAT), Seminal fluid analysis (SFA), Fertilization rate (FR) and assisted reproductive technique (ART).